PELATIHAN PENGOLAHAN JAMBU KRISTAL UNTUK MENINGKATKAN EKONOMI MASYARAKAT DESA RINGIN TUNGGAL KECAMATAN GAYAM BOJONEGORO: TRAINING ON CRYSTAL GUARANTEE PROCESSING TO IMPROVE THE ECONOMY OF THE COMMUNITY OF RINGIN TUNGGAL VILLAGE, GAYAM BOJONEGORO DISTRICT - Zumrotus Sa’diyah; Farida Isroani (Pusat Riset dan Inovasi Nasional, 2021)
The current state of the war against COVID-19 requires people to be active at home, keep their distance, wear masks and other healthy living habits. Almost all activities that we normally can do outside the home freely, such as school, work, play, lectures and others, have been restricted since the Covid-19 outbreak. On the other hand, of course, there are economic factors that make people continue to do activities outside the home. Seeing this situation, the acceleration of handling COVID-19 must be carried out thoroughly and involve all parties who take universities. In Ringintunggal village, residents work as farmers, usually growing rice, beans, soybeans, secondary crops, and others. But here there are also lots of crystal guavas owned by residents, so don't be surprised if we enter Ringintunggal village there will be lots of guava trees around people's homes, and there are several crystal guava gardens that are quite wide owned by residents. But with the abundance of guava fruit, it is not accompanied by the innovation of processed crystals. Therefore we saw that this was a problem in the village and we were moved to take action for the residents of Ringintunggal village by providing understanding and training on the potential assets owned by Ringintunggal village.